2006
DOI: 10.1073/pnas.0602932103
|View full text |Cite
|
Sign up to set email alerts
|

Role of cocaine- and amphetamine-regulated transcript in estradiol-mediated neuroprotection

Abstract: Estrogen reduces brain injury after experimental cerebral ischemia in part through a genomic mechanism of action. Using DNA microarrays, we analyzed the genomic response of the brain to estradiol, and we identified a transcript, cocaine-and amphetamine-regulated transcript (CART), that is highly induced in the cerebral cortex by estradiol under ischemic conditions. Using in vitro and in vivo models of neural injury, we confirmed and characterized CART mRNA and protein up-regulation by estradiol in surviving ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 44 publications
7
91
1
1
Order By: Relevance
“…A recent study showed that CART is highly induced by E in the cerebral cortex during ischemia, suggesting that the up-regulation of this neuropeptide by E may play a role in neuroprotection (Xu et al 2006). In our study without insult, CART mRNA was decreased by E administration but there was no effect on the peptide.…”
Section: Cart Estrogen and Neuroprotectionmentioning
confidence: 99%
“…A recent study showed that CART is highly induced by E in the cerebral cortex during ischemia, suggesting that the up-regulation of this neuropeptide by E may play a role in neuroprotection (Xu et al 2006). In our study without insult, CART mRNA was decreased by E administration but there was no effect on the peptide.…”
Section: Cart Estrogen and Neuroprotectionmentioning
confidence: 99%
“…Primary cortical neuron culture was carried out as described (Xu et al, 2006). Briefly, neurons were isolated from each embryonic cortex (E15-E17 wild-type B6 mouse) and maintained in Neurobasal media supplemented with B27 (Invitrogen, Carlsbad, CA, USA) and 25 nM glutamine at 37°C in a humidified 5% CO 2 incubator.…”
Section: Primary Cortical Neuron Culture and Treatmentmentioning
confidence: 99%
“…CART codes for a peptide that has been implicated in a variety of brain functions, including the protection offered by estradiol against ischemic brain injury in stroke and other neurodegenerative diseases (Xu et al, 2006). CART was found to be 2-fold overexpressed in pooled samples from infected animals vs. the control pool.…”
Section: Degeneration Of Synapses Associated De Genes In Bse-infectedmentioning
confidence: 99%